2009
DOI: 10.1200/jco.2009.21.9832
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate Dehydrogenase 1 Codon 132 Mutation Is an Important Prognostic Biomarker in Gliomas

Abstract: This study indicates that IDH1 codon 132 mutation is closely linked to the genomic profile of the tumor and constitutes an important prognostic marker in grade 2 to 4 gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

63
672
12
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 910 publications
(756 citation statements)
references
References 13 publications
63
672
12
9
Order By: Relevance
“…Sanson et al. (2009) analyzed the presence of the mutation of IDH1 R132H based on WHO tumor grading, which was found, from higher to lower frequency, in grade II and grade III astrocytomas and primary GMBs, with similar results found by Ducray and Shibahara groups (Ducray et al., 2011; Shibahara et al., 2011). Our primary tumors cohort presents R132H mutation mainly in grade II group, 86% of heterozygote patients belong to this group, and IDH1 R132H mutation is related to this stage (Table 3).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Sanson et al. (2009) analyzed the presence of the mutation of IDH1 R132H based on WHO tumor grading, which was found, from higher to lower frequency, in grade II and grade III astrocytomas and primary GMBs, with similar results found by Ducray and Shibahara groups (Ducray et al., 2011; Shibahara et al., 2011). Our primary tumors cohort presents R132H mutation mainly in grade II group, 86% of heterozygote patients belong to this group, and IDH1 R132H mutation is related to this stage (Table 3).…”
Section: Discussionsupporting
confidence: 71%
“…Regarding the survival analysis, previous studies demonstrated the prognostic significance of IDH1 mutations (Arita et al., 2015; Brennan et al., 2013; Ducray et al., 2011; Hartmann et al., 2010; Killela et al., 2014; Lewandowska et al., 2014; Mellai et al., 2011; Olar et al., 2012; Parsons et al., 2008; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011; Sun et al., 2013; Takano et al., 2012; Weller et al., 2009). Some authors observed that OS and PFS in IDH mutated cases were about twice longer than in wild‐type patients (Arita et al., 2015; Polivka et al., 2014), and others showed that mutation in IDH1 was an independent factor for a favorable prognosis (Brennan et al., 2013; Ducray et al., 2011; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isocitrate dehydrogenase gene mutations, estimated to occur in 70–90% of diffuse lower grade gliomas, are strongly implicated in both tumourigenesis and prognosis 23, 24, 25. Loss of heterozygosity of 1p19q, was occurred in 60–80% of oligodendroglioma and up to 45% of oligoastrocytoma 26.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similar results were obtained in the EORTC trial 26951, in that MGMT promoter methylation was prognostic for PFS in both armsradiotherapy alone and radiotherapy followed by PCV. 15 The high correlation of MGMT promoter methylation with the 1p19q co-deletion 15,57,58 and isocitrate dehydrogenase (IDH) gene mutations, 59 which are known to be favorable prognostic factors in anaplastic glioma, 14,60,61 might indicate that epigenetic deregulation of MGMT occurs in a specific pathogenetic context in anaplastic gliomas. Since MGMT promoter methylation is prognostic and not predictive for chemotherapy response in anaplastic gliomas, a methylated MGMT promoter should not be used to justify the upfront treatment of these tumors with temozolomide-based radiochemotherapy in the absence of appropriate data from studies such as CATNON (http://clinicaltrials.gov, NCT00626990).…”
Section: Anaplastic Gliomamentioning
confidence: 99%